Enhancing hair regeneration: Recent progress in tailoring nano-structured lipid carriers through surface modification strategies - Omar M. Atrooz; Nasim Reihani; M. R. Mozafari; Ahmad A. Salawi; Elham Taghavi (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Hair loss is a prevalent problem affecting millions of people worldwide, necessitating innovative and efficient regrowth approaches. Nanostructured lipid carriers (NLCs) have become a hopeful option for transporting bioactive substances to hair follicles because of their compatibility with the body and capability to improve drug absorption. Review approach: Recently, surface modification techniques have been used to enhance hair regeneration by improving the customization of NLCs. These techniques involve applying polymers, incorporating targeting molecules, and modifying the surface charge. Key results: The conversation focuses on how these techniques enhance stability, compatibility with the body, and precise delivery to hair follicles within NLCs. Moreover, it explains how surface-modified NLCs can improve the bioavailability of hair growth-promoting agents like minoxidil and finasteride. Furthermore, information on how surface-modified NLCs interact with hair follicles is given, uncovering their possible uses in treating hair loss conditions. Conclusion: This review discusses the potential of altering the surface of NLCs to customize them for enhanced hair growth. It offers important information for upcoming studies on hair growth.